팔걸이 형태에 따른 정상인의 보행변수 변화 - 이옥경(Ok Kyoung Lee); 안덕현(Duk Hyun An) (한국콘텐츠학회 논문지, 10(5), 2010)
The purpose of this study was to investigate the variations in gait parameters according to arm slings used in healthy adults. Twenty healthy adults (9 males, 11 females) participated in this study and walked at self-selected speeds on a GAITRite-instrumented carpet. They were randomly assigned conditions: without an arm sling, a care sling, a Harris hemi arm sling, a CVA sling, and a Rolyan humeral cuff sling. The following gait parameters were analyzed: the temporo-spatial parameters of gait velocity, swing phase, single support, cadence. In the comparison of parameters in each trial, step length was statistically significantly changed(p=.002). The right step length was significantly decreased in the Harris hemi arm sling and increased in the Rolyan humeral cuff sling when compared with no sling. This study found that several different types arm slings varied gait pattern in healthy adults. 본 연구의 목적은 4가지의 다른 형태의 팔걸이를 이용하여 상지의 움직임을 제한하였을 때, 보행양상에 미치는 영향을 알아보고, 기능적인 보행을 획득하기 위한 기초자료를 제공하는 것이다. 건강한 성인 남녀20명을 대상으로 미착용 상태와 단일 끈형, 해리스 편측형, 뇌졸중용, 로리안 상완 커프형 팔걸이를 착용한 상태에서 무작위 순으로 GAITRite system을 통해 보행평가를 시행하였다. 팔걸이를 착용한 동측 하지의 보장에서 유의한 결과를 나타냈다(p=.002). 팔걸이를 착용하지 않았을 때보다 해리스 편측형 착용시에 팔걸이를 착용한 동측 하지의 보장이 감소되었다(p=.001). 신전형 팔걸이인 로리안 상완 커프형 착용시에 해리스 편측형 착용 시에 비해 동측 하지의 보장이 증가되었다(p=.01). 보행속도, 유각기, 단하지 지지기, 분속수에서는 통계적으로 유의한 변화가 없었다. 앞으로의 연구에서는 팔걸이를 착용하는 환자들에게 나타나는 보행변화에 대한 연구와 기능적인 보행패턴을 획득하기 위한 운동학적 측면의 연구가 이루어 져야 할 것이다.